Digital Branding and Micro-Influencer Strategy to Create Buzz and Consumer Trust (A Study of the Glowhaven Beauty & Mind Wellness Business in Tangerang, Banten) - Eka Sapitri Pebriani; Survival Survival; Wahju Wulandari (Journal Research of Social Science, Economics, and Management, 2026)
As a new venture, GlowHaven Beauty & Mind Wellness faces significant challenges, including minimal brand awareness and low consumer trust in a saturated market. Therefore, a marketing strategy is required that not only generates buzz quickly but also fundamentally builds sustainable consumer trust. This research uses a mixed-methods approach, specifically an exploratory sequential model (qualitative to quantitative). This approach was chosen because the study not only aims to describe existing strategies (qualitative) but also to formulate and prioritize the most feasible strategies in a measurable manner (quantitative), namely through SWOT and QSPM analyses. The research subjects are individuals who possess in-depth and relevant knowledge of the research object, namely internal and external informants. The main focus of this research is the digital marketing strategy of GlowHaven Beauty & Mind Wellness, which centers on digital branding strategies (authentic content and storytelling) and the role of micro-influencers, with the goal of creating buzz and building consumer trust. The data analysis technique follows the strategic workflow established in the framework, combining qualitative and quantitative methods—specifically, qualitative analysis of initial data (data reduction), strategic matrix analysis (SWOT), and quantitative analysis of strategic priorities (QSPM). The study concluded that GlowHaven Beauty & Mind Wellness has a strong internal foundation through mindfulness narratives and authentic educational content, positioning it to capitalize on the “quiet luxury” trend and electronic word-of-mouth (eWOM) potential in Tangerang, while still needing to mitigate internal management weaknesses and the threat of audience skepticism.